2013
DOI: 10.1074/jbc.m112.416354
|View full text |Cite
|
Sign up to set email alerts
|

The Human W42R γD-Crystallin Mutant Structure Provides a Link between Congenital and Age-related Cataracts*

Abstract: Background:The mechanism of cataract formation by the recently discovered ␥D-crystallin W42R mutant is unknown. Results: Structural, biochemical, and biophysical studies revealed a partially unfolded species of the W42R mutant. Conclusion: Partially unfolded species serve as nuclei for aggregation. Significance: The properties of the W42R mutant ␥D-crystallin provide the link to the pathogenesis of age-related cataract caused by photodamaged wild-type ␥D-crystallin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 46 publications
14
88
1
Order By: Relevance
“…An increasing number of neurodegenerative and other varieties of prion and amyloid diseases are now known to be caused by misfolded structures (different 'native' structures) or by aggregation/oligomerization of intermediate conformational states, with propensity for misfolding increased by certain mutations [87,89] (figure 3). Cataracts in the human eye are also found to be caused by accumulation of misfolded proteins [90] and associated with mutations that led to abnormal folding behaviour [91,92]. As exemplified by the mouse prion protein and consistent with the general observation of evolutionary selection for kinetic stability [81], the folding and maintenance of the non-disease folded form of some of the pertinent proteins (the misfolded forms of which are implicated in diseases) is under kinetic rather than thermodynamic control [93].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 89%
“…An increasing number of neurodegenerative and other varieties of prion and amyloid diseases are now known to be caused by misfolded structures (different 'native' structures) or by aggregation/oligomerization of intermediate conformational states, with propensity for misfolding increased by certain mutations [87,89] (figure 3). Cataracts in the human eye are also found to be caused by accumulation of misfolded proteins [90] and associated with mutations that led to abnormal folding behaviour [91,92]. As exemplified by the mouse prion protein and consistent with the general observation of evolutionary selection for kinetic stability [81], the folding and maintenance of the non-disease folded form of some of the pertinent proteins (the misfolded forms of which are implicated in diseases) is under kinetic rather than thermodynamic control [93].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 89%
“…In line with the multiple causality of the disease, several distinct biochemical perturbations in vitro have been shown to cause crystallin aggregation (54,(62)(63)(64). Cataract-associated point mutations, especially ones mimicking in vivo chemical modifications, have been highly useful in dissecting the mechanism of aggregation (21,39,51) and developing interventions to modify it (65). Synergistic effects are likely among the various modes of modification or damage.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 h, all protein was digested, but E. a-BDH resisted to the trypsin digestion up to 36 h incubation (data not shown) at 37 • C. These results suggest that the change of protein structure by mutation may cause its sensitivity to trypsin digestion. In fact, Ji et al have reported similar proteolytic susceptibility phenomenon on human crystallin mutant because of a partially unfolded species [23]. In our case, nevertheless, it is possible that the mutation induced the conformational change of D194G B. s-BDH.…”
Section: Structure Of D194g B S-bdhmentioning
confidence: 73%